Corrigendum to “Multiple cranial neuropathy (a teaching case)” MSARD 2(4) (2013) 395–398 (2014)
There are few reports of the multiple cranial neuropathy variant of Guillain-Barré Syndrome (GBS). Patients usually present with facial diplegia, lower cranial nerve involvement and hypo or areflexia. It is crucial to identify promptly this unusual cranial variant but the clinical characteristics remain poorly defined. This GBS variant usually has a rapid progressive course with respiratory muscle paralysis. Most of the patients recover well, although the process is slow. We report a 54 year old man presenting with facial diplegia, progressive ophthalmoplegia, lower cranial nerve involvement, sensory ataxia and generalized areflexia. This GBS variant is very unusual and seldom described in the literature; it is oftenly misdiagnosed. The clinical features and nerve conduction studies (absent F-waves, motor conduction block) provide evidence to support a diagnosis of an acute demyelinating polyneuropathy consistent with a regional cranial variant of GBS. & 2013 Elsevier B.V. All rights reserved.